Harmonic Effects Due to the High Penetration of Photovoltaic Generation into a Distribution System - Jorge Luiz Moreira Pereira; Adonis Ferreira Raiol Leal; Gabriel Oliveira de Almeida; Maria Emília de Lima Tostes (Energies, 2021)
The growth in global electricity demand has expanded the search for new energy resources. Renewable sources such as photovoltaic (PV) systems have proven to be major alternatives. PV generators connected to distribution grids have exhibited significant growth in the last decade, so it is essential to analyse the impacts resulting from this increase. This work investigated the influence of high PV system penetration in distribution grids in terms of harmonic levels. In particular, this study addressed the distortions in voltage and current waveforms in the presence and absence of PV generators connected to a distribution grid. Additionally, the total harmonic content and the individual harmonic frequencies of voltage and current were analysed. This study was performed with an IEEE 37 bus distribution system and the Open Distribution System Simulator software (OpenDSS). The results show that the voltage limits of some phases far away from a substation can exceed the limits. Furthermore, the total harmonic distortion (THD) and individual harmonic distortion (IHD) levels for voltage and current were significantly high for harmonics of the 3rd, 5th, and 7th orders, where current levels violate the standard levels.